Uncoupling the Excitatory Amino Acid Transporter 2 From Its C-Terminal Interactome Restores Synaptic Glutamate Clearance at Corticostriatal Synapses and Alleviates Mutant Huntingtin-Induced Hypokinesia - Hirschberg, Stefan; Dvorzhak, Anton; Rasooli-Nejad, Seyed M. A.; Angelov, Svilen; Kirchner, Marieluise; Mertins, Philipp; Lättig-Tünnemann, Gilla; Harms, Christoph; Schmitz, Dietmar; Grantyn, Rosemarie (Frontiers in Cellular Neuroscience, 2022)
Rapid removal of glutamate from the sites of glutamate release is an essential step in excitatory synaptic transmission. However, despite many years of research, the molecular mechanisms underlying the intracellular regulation of glutamate transport at tripartite synapses have not been fully uncovered. This limits the options for pharmacological treatment of glutamate-related motor disorders, including Huntington's disease (HD). We therefore investigated the possible binding partners of transgenic EAAT2 and their alterations under the influence of mutant huntingtin (mHTT). Mass spectrometry analysis after pull-down of striatal YFP-EAAT2 from wild-type (WT) mice and heterozygote (HET) Q175 mHTT-knock-in mice identified a total of 148 significant (FDR <0.05) binders to full-length EAAT2. Of them 58 proteins exhibited mHTT-related differences. Most important, in 26 of the 58 mHTT-sensitive cases, protein abundance changed back towards WT levels when the mice expressed a C-terminal-truncated instead of full-length variant of EAAT2. These findings motivated new attempts to clarify the role of astrocytic EAAT2 regulation in cortico-basal movement control. Striatal astrocytes of Q175 HET mice were targeted by a PHP.B vector encoding EAAT2 with different degree of C-terminal modification. i.e. EAAT2-506X (truncation at S506), EAAT2-4KR (4 lysine to arginine substitutions) or EAAT2 (full-length). The results were compared to HET and WT injected with a tag-only vector (CTRL). It was found that the presence of a C-terminal-modified EAAT2 transgene i) increased the level of native EAAT2 protein in striatal lysates and perisynaptic astrocyte processes, ii) enhanced the glutamate uptake of transduced astrocytes, iii) stimulated glutamate clearance at individual corticostriatal synapses, iv) increased the glutamate uptake of striatal astrocytes and iv) alleviated the mHTT-related hypokinesia (open field indicators of movement initiation). In contrast, over-expression of full-length EAAT2 neither facilitated glutamate uptake nor locomotion. Together, our results support the new hypothesis that preventing abnormal protein-protein interactions at the C-terminal of EAAT2 could eliminate the mHTT-related deficits in corticostriatal synaptic glutamate clearance and movement initiation.